Strawberry Workers in Oxnard - Guillermina Diaz - Bacon, David
OXNARD, CA - Guillermina Diaz, a Mixtec immigrant from Oaxaca, picks strawberries. She and her sister support three other family members, all of whom sleep and live in a single room in a house in Oxnard, where other migrant families also live.